2002
DOI: 10.1002/tea.10053
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of the conceptual inventory of natural selection

Abstract: Natural selection as a mechanism of evolution is a central concept in biology; yet, most nonbiology-majors do not thoroughly understand the theory even after instruction. Many alternative conceptions on this topic have been identified, indicating that the job of the instructor is a difficult one. This article presents a new diagnostic test to assess students' understanding of natural selection. The test items are based on actual scientific studies of natural selection, whereas previous tests have employed hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
434
3
16

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 433 publications
(464 citation statements)
references
References 45 publications
11
434
3
16
Order By: Relevance
“…This fits with other work that suggests multiple-choice questions are not as powerful at capturing students' underlying conceptual knowledge as other types of questions (e.g., Almquist and Cronin 1988;Nehm and Reilly 2007). However, the use of student misconceptions as distracters in multiple-choice questions allows for a more complete assessment of student conceptual knowledge (Anderson et al 2002;Tanner and Allen 2005;Settlage and Odom 1995). We have successfully assessed conceptual knowledge with multiple-choice questions in a previous study (Perry et al 2008).…”
Section: Impact Of Darwinian Snails Lab On Student Performancesupporting
confidence: 81%
See 1 more Smart Citation
“…This fits with other work that suggests multiple-choice questions are not as powerful at capturing students' underlying conceptual knowledge as other types of questions (e.g., Almquist and Cronin 1988;Nehm and Reilly 2007). However, the use of student misconceptions as distracters in multiple-choice questions allows for a more complete assessment of student conceptual knowledge (Anderson et al 2002;Tanner and Allen 2005;Settlage and Odom 1995). We have successfully assessed conceptual knowledge with multiple-choice questions in a previous study (Perry et al 2008).…”
Section: Impact Of Darwinian Snails Lab On Student Performancesupporting
confidence: 81%
“…The realization that students and the general public largely misunderstand evolutionary biology principles has spurred educators and researchers to focus on the identification and correction of common misconceptions (Brumby 1984;Bishop and Anderson 1990;Anderson et al 2002). Much of this work has focused on confusions about the process of natural selection (e.g., Bishop and Anderson 1990;Settlage 1994;Jensen and Finley 1996;Nehm and Reilly 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Lawson (1983) found that prior knowledge was second only to acceptance of evolution in predicting achievement when both prior knowledge and achievement were measured using the same instrument. We are extending the study reported here with the Conceptual Inventory of Natural Selection (CINS) (Anderson, Fisher, & Norman, 2002) to examine the influence of prior knowledge on learning evolution, and look forward to other researchers using this tool to examine different curricular strategies and questions similar to those we have addressed. Lawson (1983) stated that instructors must know if students lack essential prior declarative knowledge; the CINS and tools from the forthcoming Bioliteracy project (Klymkowsky, Garvin-Doxas, & Zeilik, 2003) will provide instructors with standardized devices for quantifying prior knowledge, similar to those available for physics and astronomy (e.g., Hestenes, Wells, & Swackhammer, 1992;Hufnagel, 2002, respectively).…”
Section: Discussionmentioning
confidence: 93%
“…In this regard, the IUBMB Educational Sub-Committee, under the chairmanship of Susan Hamilton, has recently launched a more concerted effort to develop a concept inventory for the entire molecular life sciences [21], an initiative that is also being piloted in Australia as a Carrick-funded project. This whole initiative will be considerably facilitated by various other related concept inventories that have been developed, especially the biological concept inventory (BCI) project [22,23] and the conceptual inventory of natural selection (CINS) [24]. As these concept inventories develop, and we obtain greater clarification of key concepts in our field, colleagues will be in a better position to properly focus their bridging-the-gap activities.…”
mentioning
confidence: 99%